Estate Planning: Your Will - Martie Gillen; Josephine Turner (EDIS)
A will is considered to be the cornerstone of most estate plans. A will is a written legal document that takes effect at death, and is used to administer the estate, including transferring property ownership and making provisions for the care of minor or dependent children. This revised 4-page fact sheet was written by Martie Gillen and Josephine Turner, and published by the UF Department of Family, Youth and Community Sciences, March 2012.